Towards the Next World Order – Lessons from History - Adam Tooze (Intereconomics, 2025)
What might a new world order look like and who will shape it? Looking to the historical precedent of the Bretton Woods system reveals how notions of order, security and fairness were intertwined with power, hierarchy and agency. Contemporary global challenges, from geopolitical tensions to China's rise, demand a shift in perspective. Rather than seeking fixed structures, attention must turn to continuous processes of world ordering, practical collaboration and strategic engagement in an increasingly interconnected and contested world.
Keywords: F02; F50; N10; 330